Pengaruh Konsumsi SF dan Jus Jambu Biji Merah terhadap Perubahan Kadar Hemoglobin pada Remaja Puteri yang Mendapat Suplementasi Tablet SF di SMP Negeri 19 Kota Jambi Tahun 2019 - Lia Artika Sari; Nurmisih Nurmisih; Dewi Sartika (Universitas Batanghari Jambi, 2020)
Iron deficiency nutritional anemia is the most common anemia in the world. Riskesdas results showed that the prevalence of anemia of women ≥15 years old amounted to 22.7% while the prevalence of anemia in pregnant women was 37.1%. The prevalence of anemia nationally for all age groups is 21.7%. Young women are prone to anemia due to a lot of blood loss during menstruation, in addition to being exacerbated by a lack of iron intake, the need for iron in young women is urgently needed for accelerated growth and development. Coverage of young women who received blood-added tablets was 76.2% and that was not 23.8%. This research is an experimental Quasy Design study using the design of one group pre test-post test with the aim of knowing the influence of SF Consumption and Red Seed Guava Juice on changes in hemoglobin levels in Young Women who received SF Tablet Supplementation at SMP Negeri 19 Jambi City in 2019. Sampling in the study was Simple Random sampling as many as 74 students. The data was obtained from the results of the examination of the level of Hb Young women. The analysis used is univariate and bivariate. The statistical test used is the t-paired test. The average value of hemoglobin levels in Young Women before consuming SF and red seed guava juice in SMP 19 Jambi City in 2019 is 11.94 g/dl and the average value of hemoglobin in Young Women after consuming SF and guava in SMP 19 Jambi City year 2019 is 13.15 g/dl. Statistical test results There is an influence of consuming SF and guava juice on the hemoglobin levels of young women in Junior High School 19 Jambi City year 2019 with sig value (2-tailed) count 0.000 < 0.05. From the results of the study can be concluded that consuming SF in conjunction with guava juice can increase HB levels. Advice for health workers, especially midwives, to provide services related to the management of anemia in young women of high school students by doing prevention through counseling.